KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA MASA PANDEMI - Ahmad Hariyadi; Luthfa Nugraheni; Siti Aniqoh Shofwani (Equity In Education Journal, 2023)
This study aims to describe the leadership of the Principal of SMKN 2 Rembang in improving teacher performance during the Covid 19 pandemic. This research uses a qualitative approach. Data collection techniques using observation techniques, interviews and documentation. Sources of data in this study include: school principals, teachers and education staff, and students. The procedure for collecting data is carried out by observation, interviews, and documentation. Data analysis was used by adopting an interactive pattern from Miles et al (2014) which includes: data condensation, data presentation, and drawing conclusions. Checking the validity of the data is done by triangulation and member check techniques. The results of the study show that the principal's leadership in improving teacher performance during the pandemic at SMKN 2 Rembang went well. Efforts made by school principals to improve teacher performance during the pandemic are a reflection of 4 of the 7 leadership roles of school principals, including: Educator, Manager, Administrator, and Supervisor.